Desing of a cognitive behavioral program for the self-esteem of adolescent victims of family violence - Saldaña Terán, Arturo Luis Andrés (2020)
In this research in general, it was established to elaborate the proposal of a cognitive behavioral program on self-esteem in adolescent victims of family violence in an educational institution; For this, a quantitative approach, non-experimental design, cross-sectional proposition was used; Said study had a sample of 207 adolescents, to whom the Coopersmith Self-esteem inventory, school version, was applied; The values obtained were analyzed through the Excel 2016 statistical program, which revealed that in general 48% of adolescents showed very low self-esteem. On the other hand, with regard to the dimension of himself, it was possible to identify that 25% showed a very low self-esteem; while, in the social dimension, it was appreciated that 35% reflected a high level; meanwhile, in the household dimension, it was observed that 31% showed a low level; finally, in the school dimension, it was found that 35% had a very high selfesteem. Given the results presented, it was concluded by stating that adolescents who are exposed to situations of family violence are more likely to show low levels of self-esteem.